Risk factors for reduced fetal movements in pregnancy: A systematic review and meta-analysis. (December 2019) - Carroll, Lorraine; Gallagher, Louise; Smith, Valerie
Abstract: Maternal perception of reduced fetal movements (RFM) is an important clinical marker to identify women at higher risk of adverse perinatal outcomes. Preventing and reducing stillbirths can only be achieved through better detection and management of women with RFM, however the characteristics of women who present with RFM in pregnancy vary. A systematic review was conducted to explore the risk factors associated with reduced fetal movements (RFM) in pregnancy. PubMed, EMBASE, CINAHL, Maternity and Infant Care, PsycINFO and Science Citation Index were searched, from their inception date, for studies published up to 16 th May 2019. Non-randomised observational studies reporting risk factors in pregnant women presenting with a primary complaint of RFM during pregnancy were included. The quality of the included studies was assessed with the Quality in Prognosis Studies (QUIPS) tool. Meta-analyses were performed using RevMan 5.3 software for each identified risk factor where two or more studies reported on the same risk factor. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Twenty-seven studies reporting on risk factors for RFM during pregnancy were included. Women presenting with RFM during pregnancy are more likely to be Caucasian, smokers, and have an anterior placenta, oligohydramnios and polyhydramnios. No difference was found in parity or the mean age of women presenting with RFM and women who did not present with RFM. Previous caesarean section, postdates >42 weeks', and other medical conditions, including diabetes and hypertensive disorders were not predictive for RFM during pregnancy. Modifiable and non-modifiable risk factors associated with RFM in pregnancy were identified. These results can be used to raise awareness of factors associated with RFM, and prompt women to attend their maternity care provider should concerns arise.